Verification of the Theoretical Energy Requirement of Underweight, Normal Weight and Overweight Young Women Using Ergospirometry - Jachimowicz-Rogowska, Karolina; Winiarska-Mieczan, Anna; Glibowski, Paweł; Aleksandrowicz-Niedziela, Ilona; Smagała, Iwona; Bielak, Agata (Weryfikacja teoretycznego zapotrzebowania energetycznego młodych kobiet z niedowagą, prawidłową masą ciała i nadmierną masą ciała za pomocą ergospirometrii, 2023)
The research aim was to verify the theoretic energy requirement of young women and to calculate correlations between body mass index (BMI) and energy requirement, on the one hand, and the parameters obtained from bioelectrical impedance analysis on the other. The study was conducted in a group of 32 women grouped based on their BMI: underweight n = 8, normal weight n = 15, and overweight n = 9. Predictive formulas were observed to underestimate the energy requirement compared to values obtained with the use of ergospirometry. The smallest difference in Resting Energy Expenditure (REE) estimates using an ergospirometry apparatus was observed for the Cunningham equation (underweight: 1507 vs 1350 kcal) and the Harris-Benedict equation (normal weight: 1641 vs 1437 kcal; overweight: 1882 vs 1609 kcal). A significant statistical correlation was recorded in the juxtaposition of BMI to weight in the normal weight and in the overweight group. REE estimation based on formulas has only limited predictive value. Indirect calorimetry is recommended for measuring the REE rather than predictive equations.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 52-64
Keywords: energy requirement; ergospirometry; bioelectric impedance; basal metabolic rate; resting energy expenditure; zapotrzebowanie energetyczne; ergospirometria; impedancja bioelektryczna; podstawowa przemiana materii; spoczynkowy wydatek energetyczny